A cytotoxic phenotype does not predict clinical outcome in anaplastic large cell lymphomas. Issue 2 (1st February 1999) - Dukers, D F; ten Berge, R L; Oudejans, J J; Pulford, K; Hayes, D; Miseré, J F; Ossenkoppele, G J; Jaspars, L H; Willemze, R; Meijer, C J
Abstract : AIM: To investigate whether anaplastic large cell lymphomas (ALCL) expressing cytotoxic proteins have a relatively worse clinical outcome compared with ALCL lacking a cytotoxic phenotype. METHODS: 59 primary cases of ALCL originating from different sites were investigated by immunohistochemistry for the presence of the cytotoxic proteins T cell intracytoplasmic antigen (TIA-1) and granzyme B in the neoplastic cells. Since site of origin and expression of anaplastic lymphoma kinase (ALK) strongly influence prognosis, the presence of a cytotoxic phenotype was also investigated in relation to the primary site of origin (lymph node, gut, or skin) and ALK expression. The prognostic value was investigated by analysis of overall and relapse-free survival time, including Cox regression analysis. RESULTS: 39 of 59 ALCL (66%) appeared to have a cytotoxic phenotype as shown by expression of TIA-1 or granzyme B or both in the neoplastic cells. The presence of a cytotoxic phenotype did not have any influence on prognosis. Even when the survival data were corrected for site of origin and stage at presentation or were analysed separately for ALK positive and negative cases, no prognostic influence of a cytotoxic phenotype was observed. CONCLUSIONS: In primary biopsies of patients with ALCL, the presence of a cytotoxic phenotype is not related to clinical outcome of the disease.